Effects of using project-based activities on oral communicative competence of tertiary ESL learners from technical and vocational education and training - Abu Bakar, Noor Idayu (2019)
Grounded in the concept of Zone of Proximal Development in the Social Development Theory, the Communicative Competence Theory and the Gold Standard PBL model, the current study looks into the effects of using projectbased learning (PjBL) activities as a teaching strategy on the oral communicative competence of ESL learners from a Malaysian TVET higher learning institution. It also investigates the perceptions of the TVET learners in relation to the effects of PjBL as a teaching strategy. A quasi-experimental design, known as non randomised (pre-test and post-test) with control group design was employed. Forty-four students from a diploma programme at two centres of the TVET institution were purposely selected and divided into the experimental and control groups according to their intact groups. Data were collected from speaking pre and post-tests, listening pre and post-tests and a questionnaire. The study was conducted for eighteen weeks. The experimental group was taught the Communicative English course using PjBL teaching strategy as a treatment. Data from speaking and listening pre-tests and post-tests were analysed using t-tests, ANCOVA and MANOVA. The procedure began with the analysis of the pre-tests and post-tests and followed by a descriptive analysis on the data from the questionnaire. The results of t-tests showed no significant difference between groups in speaking skills (p=.870) but found a significant difference between groups in listening skills (p=.027). The results from MANOVA showed a significant difference between groups in the overall communicative competence (p=.042). Meanwhile, the results of the questionnaire revealed that a majority of TVET learners in the PjBL group were moderately competent communicators (64%) who held high perceptions of the strengths of PjBL teaching strategy in the Communicative English course (M=4.02). This study concluded that PjBL teaching strategy is more resultant than the conventional teaching strategy in improving the English language oral communicative competence of TVET learners at the higher learning institution. This work contributes to new knowledge related to the effects of PjBL on the oral communicative competence of ESL learners from the TVET field in Malaysian context. It also reinforces the ideas presented in the theories and model used in the present study. Finally, several recommendations for further research work are also given at the end of this thesis.